Piezoelectric devices for energy harvesting in building structures - Grigoryeva, Ludmila (Transfer of innovative technologies, 2021)
Devices that convert vibration energy into electricity and are capable of its accumulation (energy harvesting) are very promising both in mechanical engineering (damping oscillations with the conversion of excess energy into electricity) and in electronics and the environment (systems for energy storage and replenishment). That systems convert extra motion of engineering devises into electrical energy used for their autonomous operation or for power supply of other devices [1]. Another application is portable electronics, where energy storage devices can power or charge mobile phones or other devices. When energy sources are limited, energy harvesting plays an important role in the environment. Energy harvesting as a separate direction began to develop in the 1990s. Human, bicycle, water flow, low-frequency oscillations in mechanisms, etc. can be used as sources of mechanical energy for the piezoelectric transducer. Usually, due to steady oscillations, piezoelectric elements produce alternating electric current, showing the greatest efficiency at resonant frequencies. Most piezoelectric power sources produce power of the order of milliwatts, which is small enough for system use but sufficient for portable devices. Piezoelectric systems can convert the movement of the human body, such as the movement of legs and arms, shocks and blood pressure to obtain energy from implanted or portable sensors. Piezoelectric elements are built into running and walking roads, shoes, pavement, etc. One of the priority areas of research is the development of autonomous wireless sensors that receive energy from the measured signal, or use other ways to obtain mechanical energy. Their use becomes relevant in atypical tasks - measuring oscillations in hard-to-reach places of rotating mechanisms, seismic sensors and so on. Smart roads can play an important role in electricity generation. The incorporation of piezoelectric material into the road can convert the pressure exerted by moving cars into voltage and current.